Fuzzy clustering for segmantation of 1st trimester ultrasound fetal images - Igrejas, Getúlio (2014)
The work herein presented is a part of a broader set of tasks included in a PhD thesis which main objective is to develop an automatic measurement system for the crown-rump, nuchal translucency and biparietal measurements in ultrasound fetal images. These measurements are of extreme importance to evaluate the possible abnormal conditions of the fetus, namely chromosomal anomalies like Down’s syndrome, also known as Trisomy 21. To achieve this objective the task of segmentation, which consists inidentifying the relevant objects/structures in the ultrasound images and separate them from the non relevant ones, is of utmost importance. In this work different fuzzy clustering approaches for segmenting 1st trimester ultrasound fetal images are presented and applied for the crown-rump measurement. Results are compared with other methodologies to evaluate their performance.